Hypolipidemic Mechanisms of Ananas comosus L. Leaves in Mice: Different From Fibrates but Similar to Statins - Weidong Xie; Wei Wang; Hui Su; Dongming Xing; Guoping Cai; Lijun Du (Elsevier, 2007)
In this study, we investigated hypolipidemic mechanisms of the ethanolic extract of Ananas comosus L. leaves (AC) in mice and then determined its activities in related enzymes. The results showed that AC (0.40 g/kg) significantly inhibited the increase in serum triglycerides by 40% in fructose-fed mice. In mice induced by alloxan and high-fat diets, serum total cholesterol remained at a high level (180 - 220 mg/dl) within 7 days of removing high-fat diets but reached normal level (120 - 140 mg/dl) after AC (0.40 g/kg per day) treatment. Also, AC (0.40 and 0.80 g/kg) significantly inhibited serum lipids from the increase in Triton WR-1339-induced hyperlipidemic mice. AC (0.01 - 100 µg/ml) selectively activated lipoprotein lipase (LPL) activity by 200% - 400% and significantly inhibited 3-hydroxyl-methyl glutaryl coenzyme A (HMGCoA) reductase activity by 20% - 49% in vitro. Furthermore, 2 months of fenofibrate (0.20 g/kg) administration particularly increased mice liver weights (0.0760 ± 0.0110 g/g) while AC (0.40 g/kg) had no effect (0.0403 ± 0.0047). Taken together, these results suggest that AC will be a new potential natural product for the treatment of hyperlipidemia that exerts its actions through mechanisms of inhibiting HMGCoA reductase and activating LPL activities. Its action mechanisms differentiate from those with fibrates but may be partly similar to those with statins. It is hopeful that AC may serve as the adjuvant for fibrates. Keywords:: Ananas comosus L., hyperlipidemia, lipoprotein lipase, phenol, 3-hydroxyl-methyl glutaryl coenzyme A (HMGCoA) reductase